2021
DOI: 10.1371/journal.pone.0253805
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the association between COVID-19 and psychiatric presentations, suicidal ideation in an emergency department

Abstract: Objective To estimate the association between COVID-19 and Emergency Department (ED) psychiatric presentations, including suicidal ideation. Methods Using an interrupted time series design, we analyzed psychiatric presentations using electronic health record data in an academic medical center ED between 2018 and 2020. We used regression models to assess the association between the onset of the COVID-19 outbreak and certain psychiatric presentations. The period February 26–March 6, 2020 was used to define pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…There is increasing evidence suggesting that the response to the COVID-19 pandemic led to a disruption of health services. Several studies, mainly from Europe, North America and Asia, reported a substantial decrease in the rates of emergency department visits (Jeffery et al ., 2020 ; Wongtanasarasin et al ., 2021 ) and hospital admissions for acute medical conditions including cardiovascular diseases (Esenwa et al ., 2020 ; Pelletier et al ., 2021 ) and mental health problems (Boldrini et al ., 2021 ; Gómez-Ramiro et al ., 2021 ; McDowell et al ., 2021 ; Wyatt et al ., 2021 ) following the introduction of COVID-19 lockdowns. The effect of COVID-19 related lockdowns on outpatient care is less well researched.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence suggesting that the response to the COVID-19 pandemic led to a disruption of health services. Several studies, mainly from Europe, North America and Asia, reported a substantial decrease in the rates of emergency department visits (Jeffery et al ., 2020 ; Wongtanasarasin et al ., 2021 ) and hospital admissions for acute medical conditions including cardiovascular diseases (Esenwa et al ., 2020 ; Pelletier et al ., 2021 ) and mental health problems (Boldrini et al ., 2021 ; Gómez-Ramiro et al ., 2021 ; McDowell et al ., 2021 ; Wyatt et al ., 2021 ) following the introduction of COVID-19 lockdowns. The effect of COVID-19 related lockdowns on outpatient care is less well researched.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, annual rates of psychiatric presentations to emergency departments were largely observed to fall during the COVID-19 pandemic compared with before in data from the USA [26] and Spain [27].Inmoretargetedexaminations, however, presentation rates of individuals with psychotic disorders specifically were elevated during lockdown periods across multiple countries relative to other groups [27,28,29 & ]. Given stretched resources during the COVID-19 pandemic, these suggest that individuals with psychotic disorders may not be getting the help they need.…”
Section: Impact On Acute and Emergency Servicesmentioning
confidence: 99%
“…Recent studies have been conducted to evaluate the effects of SARS‐CoV‐2 on suicide. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 A recent meta‐analysis suggests that suicide ideation rates increased by nearly 11%, suicide attempts by 4.68%, and self‐harm by 9.63%. 26 The majority of published studies included samples of pediatric patients and we could not identify any study evaluating the effects of residing in a rural versus an urban geographic location on suicide attempts and suicide ideation.…”
Section: Introductionmentioning
confidence: 99%